Congenital Anomalies of the Breast - Caouette-Laberge, Louise; Borsuk, Daniel (Seminars in Plastic Surgery, 2013)
Poland syndrome is a combination of chest wall deformity and absent or hypoplastic pectoralis muscle and breast associated with shortening and brachysyndactyly of the upper limb. Clinical presentation varies widely; therefore, reconstructive procedures have to be adapted to the deformity, ranging from chest wall stabilization or augmentation, dynamic muscle transfer, nipple and areola repositioning, and breast augmentation using prosthesis or autologous tissue transfer. Other congenital breast anomalies include supernumerary nipple and areola (polythelia) and breast (polymastia), which can generally be found on the embryonic mammary ridge. Absence of the nipple, areola (athelia), or the breast tissue (amastia) is less frequent.
Keywords: Poland syndrome; breast; pectoralis muscle; polythelia; polymastia athelia; amastia